Destined - Pike, Aprilynne (Pike, Aprilynne. Wings, 2012)
Yuki is a rare Winter faerie, the most powerful--and deadly--of all, and Klea plans to use her to help conquer and destroy Avalon. But Klea's reach extends far beyond one wild Winter faerie. With Tamani, David, and Chelsea by her side, Laurel prepares to face what may be Avalon's final days.